“Complete individual” versus “Integral personality”. Preliminaries for considerations on human nature by Karl Marx and Ivan Kireevsky - Kroczak, Justyna (Hybris, 2018)
The aim of this paper is to compare views on human nature as held by Karl Marx and Ivan Kireevsky. Despite the fact that Marx and Kireevsky expounded two totally different philosophical world views (such as slavophilia and dialectical materialism), both can be described as socialists: one scientific, the other utopian or religious one. In this regard, it turns out that some elements of their concepts of a human being are rather common. Both of them thought that man achieves his “completeness” or “integrality” in community, not by exclusively private efforts. Kireevsky envisioned his community as an Orthodox commune, while Marx his as a classless society. Analysis shows that both anthropological concepts were more reflecting of their utopian visions than any working social model.